2020
DOI: 10.3390/molecules25112690
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Metabolic Transformation of Pharmaceuticals by Hepatic S9 Fractions from Common Carp (Cyprinus carpio)

Abstract: Water from wastewater treatment plants contains concentrations of pharmaceutically active compounds as high as micrograms per liter, which can adversely affect fish health and behavior, and contaminate the food chain. Here, we tested the ability of the common carp hepatic S9 fraction to produce the main metabolites from citalopram, metoprolol, sertraline, and venlafaxine. Metabolism in fish S9 fractions was compared to that in sheep. The metabolism of citalopram was further studied in fish. Our results suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Some in vitro studies carried out with human liver microsomes showed that citalopram can be metabolized by the isozyme of the cytochrome P450 to N-desmethylcitalopram, with a ratio of 5-10-fold for the metabolite [18]. Another in vitro study carried out with common carp (Cyprinus carpio) hepatic S9 fractions also showed the biotransformation of citalopram and sertraline into their major metabolites desmethylcitalopram and norsertraline by the isozyme of the cytochrome P450 [17].…”
Section: Ssri Metabolization In Zebrafish Eleutheroembryosmentioning
confidence: 99%
See 1 more Smart Citation
“…Some in vitro studies carried out with human liver microsomes showed that citalopram can be metabolized by the isozyme of the cytochrome P450 to N-desmethylcitalopram, with a ratio of 5-10-fold for the metabolite [18]. Another in vitro study carried out with common carp (Cyprinus carpio) hepatic S9 fractions also showed the biotransformation of citalopram and sertraline into their major metabolites desmethylcitalopram and norsertraline by the isozyme of the cytochrome P450 [17].…”
Section: Ssri Metabolization In Zebrafish Eleutheroembryosmentioning
confidence: 99%
“…Because biotransformation has the potential to reduce chemical accumulation within an organism, a question of particular concern is whether aquatic biota can appreciably metabolize these compounds. Several studies have demonstrated the metabolization of SSRIs in cell lines [17][18][19] and adult fish [11,[20][21][22], but only few research studies have been published concerning the bioaccumulation and metabolization of SSRIs in the early stages of the fish life cycle [23,24]. There is growing evidence that pollutant metabolites maintain bioactive moieties, and some are more hydrophobic and exhibit similar or even greater toxicity.…”
Section: Introductionmentioning
confidence: 99%